(untitled) (International Journal of Geoscience, Engineering and Technology, 2022)
This article aims to evaluate the suitability of a soil in the western region of Cameroon for the manufacture of earth blocks. Laterite samples taken and then passed through a 20mm mesh sieve. the soil obtained underwent a geotechnical characterization in order to know its grain size and its plasticity. the data obtained were inserted into the reference spindle of the NF XP P 13-901 standard and finally, a classification of this soil sample according to the same standard made it possible to know its acceptability for the manufacture of earth blocks. emerges that with a plasticity index of 33.35% and a proportion of 33.41% passing through the 80µm sieve, this soil sample is class B6, that is to say could be use for the production of compressed earth blocks but lacking of a few quantities of fine soil.The improvement of its granulometry as well as its stabilization with lime with regard to its high plasticity index will make it possible to increase the durability of the earth blocks produced from this soil.